Pyrazoles as Promising Scaffold for the Synthesis of Anti-Inflammatory and/or Antimicrobial Agent: A Review - A. Bekhit, Adnan; Hymete, Ariaya; El-Din A. Bekhit, Alaa; Damtew, Ashenafi; Y. Aboul-Enein, Hassan (Mini Reviews in Medicinal Chemistry, 2010)
There has been a considerable interest in the development of novel compounds with anti-inflammatory and /or antimicrobial activities. Several economical and social merits have been prospected for compounds with dual effects. Pyrazoles are an important class of compounds for new drug development that attracted much attention. Several pyrazole derivatives have been synthesized as target structures and evaluated for their biological activities. This review describes the synthesis and the development of new pyrazoles that possess anti-inflammatory and /or antimicrobial activities. The cytotoxicity of the reported compounds indicates good safety associated with many of the pyrazole derivatives. However, the need for standardized method for cytotoxicity evaluation is required for better understanding of the compounds safety and the safety-structure relationships.
Keywords: Curcumin-derived pyrazoles